(untitled) (PerCursos, 2023)
This article aims to address the (re)production of working-class space under the fragmentary socio-spatial logic, which overlaps and re-signifies the former center-peripheral dual logic. It focuses on the issue of working-class housing in Brazil beyond the materialization of commuter towns, envisioning broadening and updating the understanding of the proliferation of gated communities. The analysis emphasizes the case of Presidente Prudente, a medium-sized city located in the state of São Paulo. This research was based on an extensive bibliographic review and also interviews with residents of working-class gated communities, financed by Minha Casa, Minha Vida Program (PMCMV). Such interviews make up a larger set of records produced by a broader research on the process of socio-spatial fragmentation, for this reason, a selection was carried out here that could notably support the analysis on the (re)production of Presidente Prudente’s working-class space, identifying the valorization of the typology of gated communities, as a housing development for the PMCMV’s income ranges, and the changes related to the everyday practices of city dwellers.